Deutlicher Anstieg der Nettozuwanderung nach Deutschland - Carsten-Patrick Meier (Wirtschaftsdienst, 2013)
Die Nettozuwanderung nach Deutschland nimmt seit 2010 deutlich zu. Der maßgebliche Faktor hierfür dürfte die konjunkturelle Sondersituation in Europa sein, die sich durch einen Arbeitsmarktboom in Deutschland und eine stark gestiegene Arbeitslosigkeit in anderen Teilen Europas auszeichnet. Wanderungssalden in der aktuellen Größenordnung sind gesamtwirtschaftlich relevant, sie erhöhen das Produktionspotenzial, dämpfen den Lohn- und Preisauftrieb und haben möglicherweise Auswirkungen auf die Sozialversicherungen. – – Since 2010 net immigration to Germany has risen significantly. Net immigration to Germany in 2012 is estimated to total nearly 400 000 people. Influxes of such a magnitude have significant macroeconomic implications. While in the long run they increase the domestic labour force and hence potential output, they moderate wages and prices in the short run. This article investigates the determinants of immigration to Germany and its outlook for the coming years. It shows that differences in employment opportunities in Germany and in the rest of Europe largely explain migration fl ows. Owing to Germany's attractive labour market and the expected slow recovery in neighbouring Europe, cumulative immigration to Germany is likely to exceed two million by 2017.
Keywords: C53; F22; J61; 330; Einwanderung; Soziale Folgen; Deutschland